The Explanation of The Indices and Components of The Cafe in The Traditional and Modern Times of Iran - Hatami, Farshad; Talaei, Avideh (LPkM Universitas Bakrie, 2021)
Several factors affecting the cultural growth of the society are the correct function of social interaction, daily activities in the workplace, and increasing social action according to population growth rate need to be more evident. Review of past history showed the arrival of cafe culture in the Safavid era and Shah Abbas(I) and establishment of coffee houses in Qajar and Pahlavi era with social, economic and cultural function. In the first Pahlavi period, with the arrival of a new style of cafe from the west, the social approach and architectural style of the coffee house changed to a coffee shop. The young people of the society, as the audience, chose the coffee shop as a platform for social communication. In this article, we try to explain the course of physical and cultural developments of cafes and increase the benefit of young people from temporary urban social exchange centres as a third place (home, workplace and coffee shop) by interpreting the study examples of traditional and modern cafes in the period. We will pay attention to the Pahlavi, contemporary and modern West.